2008
DOI: 10.1186/1471-2164-9-173
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome architecture across tissues in the pig

Abstract: Background: Artificial selection has resulted in animal breeds with extreme phenotypes. As an organism is made up of many different tissues and organs, each with its own genetic programme, it is pertinent to ask: How relevant is tissue in terms of total transcriptome variability? Which are the genes most distinctly expressed between tissues? Does breed or sex equally affect the transcriptome across tissues?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 40 publications
17
45
0
Order By: Relevance
“…2A) is consistent with the previous results, which showed that the largest source of variability was tissue rather than sex or breed (Ferraz et al, 2008). The significant correlation coefficient and the GO term analysis of DEGs between brain and liver samples showed the differentially expressed genes to relate to different physiological functions and exhibited a strong correspondence to tissue functions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2A) is consistent with the previous results, which showed that the largest source of variability was tissue rather than sex or breed (Ferraz et al, 2008). The significant correlation coefficient and the GO term analysis of DEGs between brain and liver samples showed the differentially expressed genes to relate to different physiological functions and exhibited a strong correspondence to tissue functions.…”
Section: Discussionsupporting
confidence: 91%
“…From above, swine brain and liver are the important targeted tissues in the biomedical model system. Currently, although various swine tissue transcriptomic data have been obtained, more studies focused on muscle to gain insights into improving meat quality from the perspective of agricultural economy (Monego et al, 2005;Ferraz et al, 2008), the transcriptomic analysis of brains and livers in pig remains limited. The brain and liver are complementary and at the crossroads of many key neuroendocrine, metabolic and behavioral regulations.…”
Section: Introductionmentioning
confidence: 99%
“…At the present time, there are no sequences from this breed on public sequence databases. On the other hand, data from Meishan and other breeds have already been described in more than one study (Tang et al, 2007;Ferraz et al, 2008). All ESTs were deposited in the dbEST database and will not only be a valuable addition to the current archived sequences from pig, but will also provide a major resource for the comparative analysis of gene expression profiles between commercial and naturalized breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling pathway and the WNT signaling pathway. Recent study on porcine microarray expression profi ling in 16 tissues revealed the interaction between gene and tissue for differentially expressed genes targeted differentially for each tissues's transcriptome (Ferraz et al, 2008). Evidence from the recently published transcriptomics based nutritional studies performed in livestock species suggests that, with appropriate study design, it is feasible to apply transcriptomic methods successfully in animal feed and nutritional research.…”
Section: Application Of Transcriptomics In Animal and Feed Sciencesmentioning
confidence: 99%